Sleep characteristics and risk of dementia and Alzheimer’s disease: The ARIC Study - Lutsey, Pamela L (Alzheimers Dement, 2017)
INTRODUCTION: This study tested the hypotheses that late-midlife obstructive sleep apnea (OSA) and short and long sleep duration are associated with dementia over 15 years of follow-up. METHODS: 1,667 ARIC study participants underwent in-home polysomnography (1996–1998) and were followed for dementia. Dementia was defined by a) hospitalization diagnosis codes (1996–2012) and b) a comprehensive neurocognitive exam (2011–2013) with adjudication. RESULTS: OSA and sleep duration were not associated with risk of incident dementia. When using adjudicated outcomes, severe OSA (≥30 versus <5 apnea-hypopnea events/hour) was associated with higher risk of all-cause dementia [risk ratio (95%CI): 2.35 (1.06–5.18)] and Alzheimer’s disease dementia [1.66 (1.03–2.68)]; associations were attenuated with cardiovascular risk factor adjustment. Sleeping <7 versus 8–≤9 hours was associated with higher risk of all-cause dementia [2.00 (1.03–3.86)]. DISCUSSION: When adjudicated outcome definitions were employed, late-midlife OSA and short sleep duration were associated with all-cause and Alzheimer’s disease dementia in later life.